2018
DOI: 10.1080/01942638.2018.1486346
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pediatric Goal-Centered Upper Limb Spasticity Home Exercise Therapy Program for Use in a Phase-III Trial of Abobotulinumtoxina (Dysport®)

Abstract: Implementation of this home therapy program provides a standardized background of good practice against which to test the efficacy of abobotulinumtoxinA. Preliminary data show that the program is readily accepted by patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In addition to any existing physiotherapy or occupational therapy (which continued throughout the study), all children were to participate in a personalized, goal-oriented HETP to provide a standardized background of good practice after BoNT-A therapy. 12 The minimum expected requirement for the HETP was five 15-minute sessions per week and the HETP was mainly designed to support the primary treatment goal chosen. Eligibility for retreatment in the next treatment cycle was assessed at week 16; if not eligible for retreatment, they returned every 6AE2 weeks until they required retreatment, or until week 52.…”
Section: Methods Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to any existing physiotherapy or occupational therapy (which continued throughout the study), all children were to participate in a personalized, goal-oriented HETP to provide a standardized background of good practice after BoNT-A therapy. 12 The minimum expected requirement for the HETP was five 15-minute sessions per week and the HETP was mainly designed to support the primary treatment goal chosen. Eligibility for retreatment in the next treatment cycle was assessed at week 16; if not eligible for retreatment, they returned every 6AE2 weeks until they required retreatment, or until week 52.…”
Section: Methods Study Design and Participantsmentioning
confidence: 99%
“…AbobotulinumtoxinA (Dysport ® ; Ipsen Biopharm, Wrexham, UK) is a formulation of BoNT‐A proven to reduce spasticity and improve function in children with lower‐limb impairment due to CP 11 . The primary aim of this phase 3 study was to confirm the efficacy and safety of repeat abobotulinumtoxinA injections in combination with a personalized, goal‐oriented home‐exercise therapy program (HETP) 12 in reducing spasticity in children with CP. It is the first double‐blind, randomized study to compare two doses of abobotulinumtoxinA (8U/kg and 16U/kg) versus a low‐dose (2U/kg) active control group.…”
mentioning
confidence: 99%
“…For the purposes of the main study analyses, all children had to have a primary (most important) goal defined for each treatment cycle. Goals were categorized according to a list of pre-defined goal domains applicable to this population and treatment programme ( 13 ) ( Table I ) and were individually rated for importance and difficulty. Based on clinical assessment with caregiver input, investigators rated achievement on a predefined 5-point scale (–2 = much less than expected, –1 = somewhat less than expected, 0 = expected outcome, +1 = somewhat more than expected, and +2 = much more than expected).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported the primary efficacy analyses from this large, international phase III study, which showed that treatment with aboBoNT-A at doses of 8 U/kg or 16 U/kg in the affected upper limb significantly reduces spasticity in children with CP compared with the 2 U/kg low-dose control, and was generally well tolerated ( 11 , 12 ). A key feature of the study design was the inclusion of a tailored home exercise therapy programme (HETP) that was specifically developed for the study to maximize the benefits of goal-directed treatment with aboBoNT-A, and which all children followed ( 13 ). When taken overall, treatment (i.e.…”
mentioning
confidence: 99%
“…The PTMG was injected with a pre-defined volume (elbow flexors: brachialis 0.6 mL, brachioradialis 0.3 mL; wrist flexors: flexor carpi radialis 0.4 mL, flexor carpi ulnaris 0.3 mL) and maximum volumes were defined for the other upper limb muscles (Supplementary Table 1). In addition to any existing physiotherapy or occupational therapy (which was to remain stable throughout the study), all children were to participate in a personalized, goal-oriented home exercise therapy program [HETP, minimum of 5 x 15-min sessions per week (13)] to provide a standardized background of good practice after BoNT-A therapy.…”
Section: Study Treatmentmentioning
confidence: 99%